Self‐Assembled Liesegang Rings of Hydroxyapatite for Cell Culturing. Issue 5 (23rd March 2021) - Eltantawy, Mervat M.; Belokon, Mikhail A.; Belogub, Elena V.; Ledovich, Olesia I.; Skorb, Ekaterina V.; Ulasevich, Sviatlana A.
Abstract : A novel method of 3D self‐organization of patterns made of biomimetic hydroxyapatite (HA) in agar matrix is reported. The model system involves gradual ion diffusion and phase transitions of calcium phosphates. Herein, HA is precipitated for the first time in the agar gel matrix via single‐diffusion gel growth technique to aggregate the inorganic Liesegang rings (LRs). These patterns are formed as periodic structures through precipitation reaction and arise during the reagent diffusion in a polymer matrix. The concentrations of these inner and outer electrolytes, as well as pH and temperature effects on the morphologies, periodicity, stability, and number of LRs, are studied. In this study, the periodic HA Liesegang ring structures (HA LRs) are fabricated via a diffusion‐limited aggregation process. These patterns influence the C2C12 cell growth and allow to obtain the patterns formed by the cell tissue. This method can be prospective for the generation of 3D gradients in materials/3D gradient materials generation for studying the interface tissue engineering, systematic cell–biomaterial interaction, as well as for the fabrication of the stimuli‐responsive gradients to control/mimic migration of cells during the wound healing. Abstract : Self‐assembling patterns of hydroxyapatite influence C2C12 cell growth and stimulate the formation of patterns from cell tissue. This method of self‐assembly is a perspective to control the assembly of cells.